Effect of caffeine on metabolism, exercise endurance, and catecholamine responses after withdrawal - van Soeren, M. H.; Graham, T. E. (Journal of Applied Physiology, 1998)
In this study the effects of acute caffeine ingestion on exercise performance, hormonal (epinephrine, norepinephrine, insulin), and metabolic (free fatty acids, glycerol, glucose, lactate, expired gases) parameters during short-term withdrawal from dietary caffeine were investigated. Recreational athletes who were habitual caffeine users (n = 6) (maximum oxygen uptake 54.5 +/- 3.3 ml x kg-1 x min-1 and daily caffeine intake 761.3 +/- 11.8 mg/day) were tested under conditions of no withdrawal and 2-day and 4-day withdrawal from dietary caffeine. There were seven trials in total with a minimum of 10 days between trials. On the day of the exercise trial, subjects ingested either dextrose placebo or 6 mg/kg caffeine in capsule form 1 h before cycle ergometry to exhaustion at 80-85% of maximum oxygen uptake. Test substances were assigned in a random, double-blind manner. A final placebo control trial completed the experiment. There was no significant difference in any measured parameters among days of withdrawal after ingestion of placebo. At exhaustion in the 2- and 4-day withdrawal trials, there were significant increases in plasma norepinephrine in response to caffeine ingestion. Caffeine-induced increases in serum free fatty acids occurred after 4 days and only at rest. Subjects responded to caffeine with increases in plasma epinephrine (P < 0.05) at exhaustion and prolonged exercise time in all caffeine trials compared with placebo, regardless of withdrawal from caffeine. It is concluded that increased endurance is unrelated to hormonal or metabolic changes and that it is not related to prior caffeine habituation in recreational athletes.